STRUCTURE OF CLASS PLANNING FOR FUNDAMENTAL TEACHING: ANALYSIS OF DIDACTIC PROPOSALS ABOUT THE CIRCULATORY SYSTEM (Revista Contexto & Educação, 2021)
This research investigates and analyzes the structure and resources of circulatory system lesson plans, available at the Portal do Professor – Ministério da Educação. All lesson plans that cited the circulatory system were collected on the Portal (141 plans), and only those who developed the content (15 plans) were selected for the analysis of the problematization, didactic resources and evaluation. The analysis and discussion of the structure of the plans was based on two proposals for organizational methodology, called: Three Pedagogical Moments and BSCS 5E Instructional Model. The results indicate that: problematization predominates as activities and questions about previous knowledge in the introduction of the unit or subject; Digital Technologies and Information and Communication resources are frequent, especially videos; the evaluation process is under-emphasized and not detailed or indicated at the end in the form of a list of questions. The plans use some elements of the methodologies analyzed, but are their own organizations resulting from teaching practice. Identifying and understanding what is valued by teachers in the construction of the lesson plan creates possibilities for enlarge the discussions and the application of proposals that contribute to the teaching practices with reflexes in the teaching and learning process.
Keywords: Science teaching; Lesson plan; Three Pedagogical Moments; Instructional model BSCS 5E